Neoadjuvant therapy in rectal cancer: how are we choosing?. Issue 1 (29th November 2018) - Tinawi, Georges; Gunawardene, Ashok; Shekouh, Ali; Larsen, Peter D.; Dennett, Elizabeth R.
Abstract : Background: Neoadjuvant therapy has revolutionized the management of rectal cancer; however, there is a need to examine the factors driving neoadjuvant treatment allocation. This study aimed to describe patterns of treatment allocation for patients with rectal cancer at our institution and identify predictors for receiving neoadjuvant therapy, and for choice of short‐ or long‐course therapy. Methods: A retrospective review of a prospectively maintained database of 122 patients undergoing surgical resection for rectal cancer with curative intent, between 1 November 2012 and 31 October 2017. Univariate and multivariate analyses were performed to identify factors that determined which patients received neoadjuvant therapy, and whether it was short or long course. Results: Eighty‐six patients (70%) received neoadjuvant therapy. Independent predictors for receiving neoadjuvant therapy were T3‐4 tumours ( P < 0.001), node‐positive disease ( P = 0.005) and mid ( P = 0.045) or low rectal cancers ( P < 0.001). Of those receiving neoadjuvant therapy, 38 (44%) received short course and 48 (56%) received long course. Node‐positive disease was the only predictor for receiving long rather than short‐course neoadjuvant therapy ( P = 0.002). Overall, these factors predicted 76% of neoadjuvant treatment allocation. Our predictor model identified important areas of variance in our decision‐making. Conclusion: Utilizing the identified factors, it appears that consistent decisions regarding neoadjuvant therapy are being made the majority of the time. These decisions are largely driven by T and N stage as well as tumour height. Mesorectal fascia involvement, pre‐treatment carcinoembryonic antigen, age and comorbidity also influenced decision‐making to a lesser and more variable extent.